PSYCHOLOGICAL-PEDAGOGICAL FEATURES OF DEVELOPING STUDENTS' MORAL ATTITUDE BASED ON AXIOLOGICAL APPROACHES - Pardayev Sobit Abdivali oglu (Western European Studies, 2025)
In this article, the psychological-pedagogical features of developing students' moral attitude based on axiological approaches are highlighted in a certain sense.
Keywords: Axiological approaches; moral relations; psychological-pedagogical characteristics